1990-P: The Improvement of Liver Function Correlates Positively with Decreasing FABP1 Level in Chinese Patients with Obesity after Laparoscopic Sleeve Gastrectomy: A 12-Month Follow-Up Study - MA, HUIHUI; HUI, YOU; QU, SHEN (Diabetes (New York, N.Y.), 2020)
Objective: Various studies have documented the liver fatty acid-binding protein (FABP1) were closely related to liver function. However, the interrelation between the liver function and FABP1 in Chinese patients with obesity after laparoscopic sleeve gastrectomy (LSG) is unclear. Therefore, we aimed to interpret the correlation between FABP1 level and progression of liver function in obese patients, during a 12-month follow-up. Methods: This study included 131 individuals: 54 had normal weight (BMI:21.63±1.52kg/m2),77 had obesity (BMI:39.67±6.14kg/m2). The subjects were divided into three tertiles (Q1, Q2, and Q3) according to FABP1 levels: Q1, <16.35ng/ml; Q2, 16.35∼34.30ng/ml; Q3, >=34.30ng/ml. FABP1 levels were measured using ELISA. Results: Serum FABP1 levels were significantly higher in patients with obesity (29.71±22.35 ng/ml, P< 0.001) than normal weight individuals (13.70±9.48 ng/ml). FABP1 level was decreased at 6 and 12 months after LSG (15.00±10.27ng/mL, P<0.001, and 12.74±7.64 ng/mL, P<0.001).At baseline, compared to the bottom tertile (Q1), middle (Q2) and upper (Q3) tertile of FABP1 were related to higher liver enzyme level. Besides, after LSG, liver enzymes declined rapidly in Q2 and Q3 than Q1. Correlation analysis found that the decrease in FABP1 level was positively correlated with the decrease in ALT, AST, and γ-GT at 6 and 12 months after LSG. After adjusting for age, sex, ΔTC, ΔTG, ΔHDL, ΔLDL, ΔFBG, ΔFINS, ΔFCP, ΔFFA, and ΔUA, linear regression analysis revealed the decreased FABP1 levels was only positively correlated with the alterations of ALT (R2=0.769, P=0.001) and AST (R2=0.836, P<0.001) at 12 months after LSG. Conclusion: Our results suggested obesity was strongly associated with up-regulated serum FABP1 level. In addition, the improvement of liver function was positively correlated with changes in FABP1 at 12 months in Chinese patients with obesity after LSG.